The Effect of Fin-tech Usage Towards Millenial's Financial Literacy - Astari, Yen Syifa; Damayanti, Sylviana Maya (Journal of Business and Management, 2020)
Abstract. The purpose of this study is to determine the effect of the use of fin-tech on millennial financial literacy in Jakarta and determine the level of millennial financial literacy in Jakarta. This research also aims at giving recommendations to improve financial literacy through fin-tech. The data collection technique was by distributing questionnaires to 385 respondents in Jakarta. By using multiple linear regression analysis, this study found that simultaneously transactional activity, informational activity, perceived usefulness, and perceived ease of use affect the level of millennial financial literacy in Jakarta. Partially, transactional activity, perceived usefulness, and perceived ease of use respectively affect the level of millennial financial literacy in Jakarta. Millennial financial literacy in Jakarta is 72,98, which means the level of Millennials financial literacy in Jakarta is intermediate level.Keywords: Fin-tech, Financial literacy, Transactional Activity, Informational Activity, Perceived Usefulness, Perceived Ease of Use